Three cases utilizing the Hidden Incision Endoscopic Surgery approach to port placement during penile inversion vaginoplasty utilizing a peritoneal flap. Issue 5 (October 2022) - Bajakian, Thalia; Hannallah, Arthi; Cowan, Andrew; Baker, Zoë; Sparks, Stephen; Lee, Jessica; Kokorowski, Paul
Summary: Introduction: Younger transgender patients undergoing penile inversion vaginoplasty (PIV) after pubertal suppression often require modified techniques to augment neovaginal tissue. Peritoneal flap vaginoplasty (PFV) is a well-established technique for improving neovaginal depth. Utilizing a Hidden Incision Endoscopic Surgery (HIdES) approach to port placement improves cosmetic outcomes of this identity-affirming procedure. Objective: This video shows the efficacy of the HIdES port placement configuration on the daVinci robot for peritoneal flap creation and closure during PIV using the modified laparoscopic Davydov procedure. Materials and methods: Three young adult transgender females who had not undergone laser hair removal/epilation underwent PIV with robotic PFV utilizing HIdES port placement. The anterior superior iliac spine (ASIS) was demarcated bilaterally, and ports were placed at or below these lines. Two surgical teams, external genitoplasty and internal peritoneal flap closure via daVinci Xi robot, worked simultaneously. Results: All patients underwent successful robotic assisted PIV with HIdES port placement. All patients had similar postoperative courses of return of bowel function with flatus on postoperative day (POD) 2, vaginal dressing, urethral catheter removal, and initiation of vaginal dilation on POD 5–6, and hospital discharge between POD 5–8. Conclusion: We present our initial experience with robotic/laparoscopic PFV using a hidden incision approach. This technique allows for excellent neovaginal depth with improved abdominal wound aesthetics.